The influence of a pulsed-DC field on the growth of the Fe2B layer and the electrical behavior of the boriding media. (April 2023) - Castillo-Vela, L.E.; Mejía-Caballero, I.; Rosales-Lopez, J.L.; Olivares-Luna, M.; Contreras-Hernández, A.; Keddam, M.; Campos-Silva, I.
Abstract: Novel results about the growth kinetics of Fe2 B layers produced by pulsed-DC powder-pack boriding (PDCPB) on AISI 1018 and 4140 steels were obtained. In the process, a DC-field is applied to ionize the B atoms and implements a programmable electronic control device (PECD) to maintain a constant B flux on both surfaces of the material. During PDCPB, the electrical resistivity (ER) was reduced due to the percolation of KBF4 in the boriding media. Nevertheless, the increase of ER was caused by the depletion of KBF4 after 1000s of the current induction. The PDCPB enhanced the growth kinetics of the Fe2 B layer around of 9% for both borided steels compared to those estimated in the conventional powder-pack process. Highlights: A low potential boriding media allows the formation of Fe2 B layer. The pulsed-DC field enhances growth kinetics of the Fe2 B layer. The electromigration energy contribution decreases boron activation energy in Fe2 B. Boron activation energy in Fe2 B is 9% lower than traditional powder-pack boriding. DC field modifies the electrical behavior of boriding media due to Joule effect.